Analysis of Food Preferences for Policy: A Case Study of the Latino Community in Somerville. - Caplan, Emily B. (Tufts Archival Research Center, 2014)
Abstract: Obesity is a rising health concern in the United States, and availability of healthy foods in grocery stores is an important factor. Lacking from the current literature in this area is a culturally specific analysis of what drives food preferences and a consideration of culture in the development of healthy food policies. This study examines the motivations behind food preferences in a specific Latino community in East Somerville. Based on study findings, the discussion section includes policy suggestions to increase availability of healthy foods in the three Latino bodegas of study. Using a quantitative Nutrition Environment Measures Survey for stores (NEMS-S) that I worked on last summer in Guatemala to determine the availability of healthy food options in three Latino bodegas, and qualitative interviews to determine what drives consumer food preferences, I tested three hypotheses: 1. The foods found in the three Latino bodegas will apply more closely to the NEMS-S survey created in Guatemala than the general NEMS-S survey created for U.S. stores, meaning that consumer buying preferences in these stores are molded more by culture of origin than by culture of residence, 2. There will be a general lack of healthy food options in these stores indicated by the results of the NEMS-S surveys, and 3. Consumers will have reasons other than food for why they choose to shop at these stores: e.g. for community, social, and cultural aspects. Results will be used to determine whether healthy food policies are needed in these stores and then to suggest policy options based on consumer preferences.